Penerapan Teknik Laser Cut pada Busana Convertible dengan Sumber Ide Bunga Daisy - Aden Noor Syukurian Anikmah; Irma Russanti (Universitas Negeri Surabaya, 2025)
In line with the changing lifestyles of modern society, the demand for practical, versatile, and efficient clothing has also increased. Convertible fashion has emerged as one response to this need. However, the decorative elements applied to convertible clothes are mostly limited to surface design techniques such as traditional textiles or digital printing. This highlights the need to explore other more creative and dimensional decorative techniques, one of which is fabric manipulation through laser cutting. This study aims to describe the process and final outcome of applying laser cut techniques as aesthetic elements to convertible clothes with daisy flower as idea source. The research method used is the Double Diamond Model, which consists of four stages: Discover, gathering information related to laser cut, convertible fashion, and daisy flowers; Define, compiling ideas into a cohesive concept through a moodboard; Develop, developing the design and producing the product; and Deliver, finalizing and evaluating the product. The final outcome of this research is the creation of a construction-type convertible clothes with two different styling options, featuring aesthetic laser cut elements with a daisy flower motif on denim material.